Biological mesh reconstruction versus primary closure for preventing perineal morbidity after extralevator abdominoperineal excision: a multicentre retrospective study. (26th July 2020) - Sancho‐Muriel, J.; Ocaña, J.; Cholewa, H.; Nuñez, J.; Muñoz, P.; Flor, B.; García, J. C.; García‐Granero, E.; Die, J.; Frasson, M.
Abstract: Aim: The aim of the study was to compare the incidence of perineal hernia and the perineal wound morbidity following extralevator abdominoperineal excision (ELAPE) between two groups – primary perineal closure and reconstruction with a biological mesh. Method: One hundred and forty‐seven consecutive patients who underwent ELAPE for primary rectal cancer between January 2007 and December 2018 in two tertiary referral centres were retrospectively identified from prospective databases. Perineal closure was carried out via primary closure or with a biological mesh (porcine dermal collagen mesh). Outcome measures were perineal hernia and perineal wound morbidity (infection, dehiscence, persistent sinus and chronic pain). Results: A total of 139 patients were included in the study. A prophylactic mesh was used in 80 (57.5%) and primary closure was practised in 59 (42.4%) patients. The median follow‐up was 30 (interquartile range 46.88) months. Thirty patients (21.6%) developed perineal hernia. No significant differences were found between prophylactic mesh and primary closure (16.3% vs 23.3%, P = 0.07). The median period between surgery and hernia diagnosis was 8 months in the primary closure group and 24 months in the mesh group ( P < 0.01). Perineal wound morbidity was significantly higher in the prophylactic mesh group (55% vs 33.9%, P < 0.01). Conclusion: In our study, the use of a biological mesh did not reduce the rate of perineal hernia, although it did delay its appearance. Perineal closure using a biological mesh may increase perineal morbidity, both acute and chronic.